Legal Protection Of Brand Rights And Geographical Indications For Toraja Coffee - Mutiara Nabila Rizqi; Upik Mutiara (Jurnal Hukum Volkgeist, 2023)
Geographical Indication is one of the Intellectual Property Rights that protects things that have features, attributes, or reputations related to the location from which they originated. Arabica coffee, which is native to Toraja South Sulawesi, has distinct attributes that distinguish it from other types of coffee, earning it a reputation as one of the world's best. The "TORAJA" brand, on the other hand, misleads customers about its uniqueness. Arabica coffee's reputation will be jeopardized if it is not from Toraja and its quality differs from that of Toraja coffee. To preserve Torajan arabica's reputation and coffee farmers, geographical indication registration on this Torajan arabica coffee is required. Geographical Indications must be legally protected in order to identify whether individuals are communal or collective. Belonging to the community in the registered Geographical Indication region is what the communal community character entails.